IMPLEMENTASI KOLABORASI QUANTUM LEARNING DAN COOPERATIVE LEARNING UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN MATA KULIAH STRATEGI BELAJAR-MENGAJAR - Sri Sumaryati; Sukirman Sukirman (PAEDAGOGIA, 2010)
The purpose of this research is: (1) to improve teaching learning processthrough the implementation of collaborative method between quantum model andcooperative learning, (2) to increase lecturer's competence in implementing variousstrategies and models in teaching learning process, (3) to improve student's competencein understanding the subject of Learning Strategies. This research is a classroom actionresearch. It consists of two cycles. Documentation, observation and test method areapplied in collecting data. The result of the research shows that the using of collaborativemethod between quantum model and cooperative learning in teaching learning processof Learning Strategies : (1) can make the student more active physically and mentally, (2)can make the students more successful in learning the subject of Learning Strategies. Thiscan be seen form quiz 1 (67,5) and quiz 2 (77,9).